Age‐adjusted comorbidity and survival in locally advanced laryngeal cancer. Issue 9 (13th May 2018) - ,; Mulcahy, Collin F.; Mohamed, Abdallah S. R.; Kanwar, Aasheesh; Hutcheson, Katherine A.; Ghosh, Alokananda; Vock, David; Weber, Randal S.; Lai, Stephen Y.; Gunn, Gary Brandon; Zafereo, Mark; Morrison, William H.; et al.
Abstract: Background: The purpose of this study was to quantify the relationship among age, pretreatment comorbidity, and survival outcomes in patients with locally advanced laryngeal cancer. Methods: Baseline comorbidity data were collected and age‐adjusted Charlson Comorbidity Index (CCI) was calculated for each case. Kaplan‐Meier and Cox proportional hazards modeling were used to determine associations with survival. Results: For 548 patients, with a median age of 59 years (range 31‐91 years), 58% were treated with larynx preservation and the rest with total laryngectomy and adjuvant radiotherapy (RT). Two hundred thirty‐eight patients (43%) had at least 1 comorbidity each. Cardiovascular diseases were the most common comorbidities (19%). The 5‐year overall survival (OS) for patients with CCI ≤3 (n = 442) were superior to CCI >3 (n = 106; 60% vs 41%; P < .0001), although the 5‐year disease‐specific survival (DSS) rates were not significantly different. The 5‐year noncancer CSS was better for age‐adjusted CCI ≤3 (88% vs 67%; P < .0001). Conclusion: The age‐adjusted CCI is a significant predictor of noncancer CSS and OS for patients with locally advanced laryngeal cancer but is not associated with DSS.